Expectancy-Based Strategic Processes Are Influenced by Spatial Working Memory Load and Individual Differences in Working Memory Capacity - Ortells, Juan J.; De Fockert, Jan W.; Romera, Nazaret; Fernández, Sergio (Frontiers in Psychology, 2018)
The present research examined whether imposing a high (or low) working memory (WM) load in different types of nonverbal WM task could affect the implementation of expectancy-based strategic processes in a sequential verbal Stroop task. Participants had to identify a colored target (a red vs. green patch) that was preceded by a prime word (RED or GREEN), which was incongruent with the target color on 80% of the trials, and congruent on 20% of trials. Previous findings have shown that participants can strategically use this information to predict the upcoming target color, and avoid the standard Stroop interference effect. The Stroop task was combined with different types of nonverbal WM task. In Experiment 1, participants had to retain sets of four arrows that pointed either in the same direction (low load) or in different directions (high load). In Experiment 2, they had to remember the spatial locations of four dots which either formed a straight line (low load) or were randomly scattered in a square grid (high load).In addition, participants in the two experiments performed a change localization task to obtain a measure of their WM capacity (WMC). The results in both experiments showed a reliable interaction between prime-target congruency and WM load. When participants performed the Stroop task under high WM load, they were unable to efficiently ignore the incongruence of the prime, as they consistently showed a standard Stroop effect, regardless of their WMC. Under a low WM load, however, a strategy-dependent (reversed Stroop) effect was observed. This ability to ignore the incongruence of the prime was modulated by WMC, such that the reversed Stroop effect was mainly found in higher WMC participants. The findings that expectancy-based strategies on a verbal Stroop task are modulated by load on different types of spatial WM tasks point at a domain-general effect of WM on strategic processing. The present results also suggest that the impact of loading WM on expectancy-based strategies can be modulated by individual differences in WMC.